Strategi Digital Marketing atas Produk dan Layanan yang Ditawarkan dalam Bisnis Prostitusi Online - Habib, Muhammad Alhada Fuadilah; Ramadhani, Marina; Fatkhullah, Mukhammad; Diniati, Bintis Ti’anatud; Istiqoma, Istiqoma (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2024)
The massive advances in digital technology have brought about major changes in business. Various economic activities ranging from marketing, sales, payments, to the distribution of goods have been accelerated by various digital platforms. The same acceleration also occurred in the prostitution business and its various business lines. Even though it is a business that violates moral and religious values, in fact, prostitution that uses online media is growing rapidly. Social media, such as Twitter, Whatsapp, MeChat, and OnlyFans are often used as transaction media for online commercial sex workers. The purpose of this research is to examine digital marketing strategies as well as the products and services offered in the online prostitution business. This study uses digital-based data collection techniques, by conducting online in-depth interviews, digital observations, and digital literature studies. The informants in this study were commercial sex workers and their consumers. This research is also supported by online observations and literature studies. The results of the study show that digital marketing of the online prostitution business includes: (1) utilizing websites that have been optimized for search engines, (2) utilizing social media and creating persuasive content, (3) integrating more than one online media, and (4) ) using digital advertising and e-mail services. Meanwhile, the products and services offered include: (1) audio-visual products, (2) visual products, (3) dating partners, (4) massage services, and (5) intercourse services.